2019
DOI: 10.1186/s12885-019-6225-9
|View full text |Cite
|
Sign up to set email alerts
|

Migration of gastric cancer is suppressed by recombinant Newcastle disease virus (rL-RVG) via regulating α7-nicotinic acetylcholine receptors/ERK- EMT

Abstract: Background: Nicotinic acetylcholine receptors (nAChRs) have been reported to be overexpressed in malignancies in humans and is associated with tumorigenesis and cell migration. In previous studies of gastric cancer, alpha7 nicotinic acetylcholine receptor (α7-nAChR) overexpression leads to epithelial-mesenchymal transition (EMT) and promotes the migration of gastric cancer cells. Recombinant avirulent LaSota strain of Newcastle disease virus (NDV) expressing the rabies virus glycoprotein (rL-RVG) may promote a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…YAP has been reported to promote GC cell survival and migration/invasion via the ERK pathway [ 37 ]. Recombinant Newcastle disease virus (rL-RVG) inhibits GC migration by regulating α7-nAChR-MEK/ERK-EMT [ 38 ]. Consistent with previous studies, HAVCR1 was highly expressed in GC cells, and HAVCR1 knockdown induced apoptosis and inhibited proliferation, migration, invasion, and EMT.…”
Section: Discussionmentioning
confidence: 99%
“…YAP has been reported to promote GC cell survival and migration/invasion via the ERK pathway [ 37 ]. Recombinant Newcastle disease virus (rL-RVG) inhibits GC migration by regulating α7-nAChR-MEK/ERK-EMT [ 38 ]. Consistent with previous studies, HAVCR1 was highly expressed in GC cells, and HAVCR1 knockdown induced apoptosis and inhibited proliferation, migration, invasion, and EMT.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction mainly matters in neuronal disorder, nevertheless, recent reports emphasized the role of nicotinic acetylcholine receptors in oncogenesis. The blockage of a7nAChR reversed acetylcholine-induced cell migration and invasiveness in NSCLC cells and gastric cancer cells via blocking signaling by MEK/ERK pathway [156,157]. Moreover, in gastric cancer, cholangiocarcinoma, this receptor inhibition was connected with reduced expression of EMT markers [158].…”
Section: Other Carcinogenesis Modulating Effects Of Trp Metabolitesmentioning
confidence: 91%
“…Furthermore, NDV–GFP may provide a more sensitive method than conventional cytology for detecting gastric cancer. Bu et al, 2019a and Bu et al, 2019b reported that the recombinant LaSota strain expressing rL-RVG (rabies virus glycoprotein) suppressed nAChRs (nicotinic acetylcholine receptors) to reduce cell migration and EMT (epithelial to mesenchymal transition) in gastric cells. Moreover, rL-RVG suppressed the growth of gastric cancer subcutaneous tumor cells in vivo ( Bu et al, 2019a ).…”
Section: Preclinical Application Of Newcastle Disease Virus In Variou...mentioning
confidence: 99%